Características sociodemográficas, clínicas y médicas en pacientes con hipertensión arterial diagnosticada de los territorios vecinales 01, 03 y 38 del distrito de Trujillo-2013” - Condori Cabrera, Yavelia Miriam (2013)
We performed a cross-sectional descriptive study in order to determine which sociodemographic, clinical and medical characteristics in patients with hypertension diagnosed in the territories Neighborhood: 01, 03 and 38 of the District of Trujillo. The population consisted of 37 patients, 8 men and 29 women. Home visits were conducted in which a story filled pharmacotherapeutic (DADER method) for each patient, which includes health problems, medications used; were recorded blood pressure, weight, height, waist circumference and waist hip ratio. We found that most patients is in the range of 60-69 years, with the majority of them women, 32,43% have an average education level, alcohol and snuff was higher in men than in women, women are more conscious of diet and do more exercise the 45,95% of patients are overweight and obese 27,03% type I, 70% of patients do not have controlled their disease. Found 18% of dyslipidemias, diabetes 14%, 11% gastritis and 9% varicose veins as hypertension related pathologies. In conclusion states that obesity is a major risk factor for this population, the female is the better watch their eating habits and lifestyles, the majority of the population does not have controlled their disease, dyslipidemia and diabetes are most common associated diseases of the study population, the most commonly used drugs are Enalapril and Losartan.